Structural evolution characteristics and genesis of buried hill faults in the Chengdao–Zhuanghai area - Wang, Zhiwei; Zhang, Kai; Wu, Qunhu; Zhou, Hongke; Yu, Shina; Li, Yang (Frontiers in Earth Science, 2023)
The buried hills in the Chengdao–Zhuanghai area are rich in oil and gas resources, and their structures exhibit complex styles with unique evolution characteristics. Based on the latest exploration progress in this region, the structural characteristics and active parameters of the buried hill faults in this region were quantitatively analysed following the balanced section technology. In addition, the structural evolution process of the study area was reproduced by combining the structural physical simulation experiment. Furthermore, its spatiotemporal evolution characteristics and genesis mechanisms were systematically addressed. As observed, the study area developed three fundamental sets of fault systems: NW-trending extensional strike-slip fault, NNE-trending left-handed compression–torsion fault, and near-EW-trending extensional fault. Further, the study area was segmented into six buried hills: west-row hill, middle-row hill, east-row hill, Zhuanghai buried hill, Zhuangxi buried hill, and Changdi buried hill. The inner fault at the NW-trending buried hill is a strike-slip extension fault formed under the influence of the right-lateral strike-slip activity of the NW-trending Chengbei fault from the Late Jurassic to Early Cretaceous. In particular, the NNE-trending fault was a left-handed compression–torsion fault formed under the left-handed strike-slip activity and regional compression stress field of the Tanlu fault zone. The near-EW fault was closely related to the near-SN extension stress field in the late Late Cretaceous. Since the late Triassic, the study area experienced six evolution stages, namely, overall uplift erosion (T3), overall coating deposition (J1+2), fault segmentation (J3-K1), extrusion uplift differentiation (K2), middle buried hill differentiation (E), and overall stable subsidence (N-Q). Its tectonic evolution was primarily controlled by the significant variations in the tectonic stress field in the study area as well as its adjacent areas since the late Triassic, which were controlled by the tectonic stress field.